2010
DOI: 10.1159/000276580
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality, Mood, Alertness and Their Variability in CKD and ESRD

Abstract: Background/Aims: Little is known about the association of chronic kidney disease (CKD) with sleep quality, mood, and alertness. In this report, we assessed these symptoms among patients with advanced CKD (stages 4–5) and those with end-stage renal disease (ESRD) and compared them to healthy controls without known kidney disease. Methods: Patients were recruited from local dialysis units, outpatient nephrology clinics and the Thomas E. Starzl Transplant Institute. Healthy control subjects matched for age, gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 82 publications
2
17
1
3
Order By: Relevance
“…Their performance in physical activities further aggravates the anxiety of these patients and their physical and mental burden by affecting the quality of sleep as evidenced by the research of Kwabena and Awuah [ 1 ]. According to Roumelioti et al [ 14 ], dialysis dependency was associated with poor sleep quality, and hemodialysis patients with sleep-disordered breathing were found to have poor sleep quality compared with those not on hemodialysis [ 15 ]. Our results showed that patients were classified as bad sleepers at the total PSQI score (8.8 ± 2.8) compared to previous studies which classified patients as poor sleepers when having score > 5.5 in PSQI [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their performance in physical activities further aggravates the anxiety of these patients and their physical and mental burden by affecting the quality of sleep as evidenced by the research of Kwabena and Awuah [ 1 ]. According to Roumelioti et al [ 14 ], dialysis dependency was associated with poor sleep quality, and hemodialysis patients with sleep-disordered breathing were found to have poor sleep quality compared with those not on hemodialysis [ 15 ]. Our results showed that patients were classified as bad sleepers at the total PSQI score (8.8 ± 2.8) compared to previous studies which classified patients as poor sleepers when having score > 5.5 in PSQI [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“… 16 Moreover, sleep and mood disturbances are common among patients on dialysis and are significantly associated with worse survival and health-related QoL perceived. 16 , 19 These psychological alterations inexorably lead to a reduced compliance to the treatment and an increase in hospital admissions. 20 …”
Section: Introductionmentioning
confidence: 99%
“…Sleep disorders, including delayed sleep onset, frequent awakening, restless leg syndrome, insomnia, and daytime sleepiness, are frequent in patients with end stage renal disease (ESRD) (2,(4)(5)(6)(7)(8). These symptoms affect sleep quality and consequently the quality of life of these patients (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%